ESTABILIDADE DOS ANTÍGENOS DE PAREDE CELULAR DE PARACOCCIDIOIDES BRASILIENSIS - Assis, C.M.; Da Silva, D.F.; Zamboni, I.M.; Oliveira, L.E.; Vicentini, A.P. (Revista do Instituto Adolfo Lutz, 2002)
Ver PDF.